Managerial Competence of Functional Position: Implementation Study of Position Equalisation Policy - Rivai, Muhammad Yan; Subhilhar, Subhilhar; Irmayani, Tengku (PT FORMOSA CENDEKIA GLOBAL, 2024)
The North Padang Lawas District Government has implemented a bureaucratic simplification policy to simplify the organizational structure and equalize administrative positions into functional positions. However, this policy faces resistance and discomfort among employees, especially functional officials. This study aims to determine the managerial competence of functional civil servants at the Personnel and Human Resources Development Agency of North Padang Lawas Regency. The research method used is descriptive qualitative, collecting data through interviews, observation, and document analysis. The results showed that the implementation of the policy has not resulted in significant changes; besides that, there has yet to be integration of the collaboration work system, which is only limited to working on their respective roles and functions. The stages of simplifying the bureaucracy are still being adapted and transitioned.